1992
DOI: 10.1007/bf00180207
|View full text |Cite
|
Sign up to set email alerts
|

Failed lumbar spinal surgery

Abstract: Failures and poor results of 160 patients after lumbar spinal surgery between 1980 and 1984 were analysed retrospectively. A self-rated questionnaire carried out 12 months after operation revealed 20 poor results; these occurred most commonly after multiple operations, decompression and fusion as compared to disc excision. The commonest cause was failure to recognise abnormal pain behaviour before operation. A more careful preoperative assessment should reduce the incidence of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Dhar et al have suggested that the commonest cause of failure is incorrect assessment and selection for operation and stress the importance of psychological testing and analysis of any compensation claims [6]. We agree, but wish to emphasise the significance of the indications for operation and the surgical technique.…”
Section: Discussionmentioning
confidence: 88%
“…Dhar et al have suggested that the commonest cause of failure is incorrect assessment and selection for operation and stress the importance of psychological testing and analysis of any compensation claims [6]. We agree, but wish to emphasise the significance of the indications for operation and the surgical technique.…”
Section: Discussionmentioning
confidence: 88%
“…A well studied group consisted of failures and poor results in 160 patients after lumbar spinal surgery between 1980 and 1984; they were analyzed retrospectively. 11 A self-rated questionnaire carried out 12 months after operation revealed 20 (12.5%) poor results. These occurred most commonly after multiple operations, or decompression and fusion as compared to disk excision.…”
Section: Operative Treatmentmentioning
confidence: 99%